“I’m Just Not Good at Math!” Rethinking What You Know About Mathematics - Pohl, Katherine Ann (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
There are many misconceptions regarding mathematics that produce negative student dispositions in a classroom. Such misconceptions are not fact based but are due to an ineffective, fixed mindset where a student limits their abilities based upon low self-efficacy and self-concept. Fixed mindsets fuel negative attitudes toward mathematics and can contribute to math anxiety. Studies have shown that the brain can grow and develop throughout a person’s life is partially dependent upon one’s mindset and experiences. Mathematics teachers can utilize a growth mindset where students have high self-efficacy and self-concept to promote positive dispositions toward mathematics. In doing this, teachers must model high teacher efficacy themselves and believe in student ability by disregarding false limitations set by prior experiences.